The Use of Mind Mapping Technique in Learning Chinese Vocabulary at Private Senior High School in Makassar - Mir'ah Azizah (Interference: Journal of Language, Literature, and Linguistics, 2022)
Abstract. This study aims to determine the effectiveness of the Mind Mapping Technique in learning Chinese vocabulary. The author uses the Quantitative-Qualitative Research method in quadrant I, namely by using pre-test, mind mapping techniques, post-test, and observation guidelines as research instruments. The data is then analyzed to get the average score and the percentage of student progress. The sample of this study was 28 students from Golden Gate School Makassar. The results showed that students were very enthusiastic in learning to use Mind Mapping Techniques and the class atmosphere became very pleasant. In addition, students' ability to master Chinese vocabulary has increased after applying the Mind Mapping Technique. The mean score of the students in the pre-test was 47.5 which was classified as very low score. On the other hand, the general average of students in the Post-test is 81.25 which is classified as a good score. The percentage of Student Improvement scores also increased to 80.78%. This proves that the use of the Mind Mapping Technique is very effective in learning Chinese vocabulary. Keywords: Vocabulary, Chinese Language, Technique, Mind Mapping